School Policy in Supporting Teacher Career Development at MIN 50 Bireuen - wildanum; Susi Yusrianti; Khairiani Khairiani (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study explores how school policies are formulated and applied to support teacher career development in the context of an Islamic school in MIN 2 Bireuen. This study using a qualitative descriptive method, data were collected through interviews, direct observations, and document analysis involving key stakeholders such as the principal, vice principal, and selected teachers. The results reveal that MIN 50 Bireuen has initiated several strategies, including opportunities for further education, internal coaching programs, and performance-based incentives. While these policies are driven by the strong leadership of the principal and a supportive organizational climate, the study also identifies several barriers, such as limited funding allocation, inadequate institutional systems, and rigid bureaucratic procedures. The findings emphasize that effective school-level policies can significantly motivate teachers to pursue professional growth, provided they are aligned with the school’s vision, supported by adequate resources, and implemented transparently. This study recommends a more structured and culturally responsive policy framework to ensure the sustainable development of teacher professionalism within Islamic educational institutions.